2018
DOI: 10.1007/s10068-018-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kombucha on gut-microbiota in mouse having non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver disorders. Possible links have been recently found between the gut-microbiota and the host metabolism in development of NAFLD and obesity. Therefore, understanding the changes in intestinal microbiota during the progression of NAFLD, is important. In this study, the effect of Kombucha tea (KT), obtained by microbial fermentation of sugared black tea, was investigated on gut-microbiota during the progression of NAFLD. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…The level of Erysipelotrichia is suggested to be important bacterial marker of susceptibility to choline deficiency‐induced fatty liver disease. [ 58 ] High levels of Erysipelotrichia in human fecal microbiota are associated with hepatic steatosis and correlated to higher risk of developing fatty liver on low‐choline diet. [ 59 ] It is reported that the attenuation of the MCD diet‐induced NAFLD by the treatment of 2,3,5,4′‐tetrahydroxy‐stilbene‐2‐O‐β‐D‐glucoside (TSG) was seemingly associated with the reduced abundance of Erysipelotrichaceae .…”
Section: Discussionmentioning
confidence: 99%
“…The level of Erysipelotrichia is suggested to be important bacterial marker of susceptibility to choline deficiency‐induced fatty liver disease. [ 58 ] High levels of Erysipelotrichia in human fecal microbiota are associated with hepatic steatosis and correlated to higher risk of developing fatty liver on low‐choline diet. [ 59 ] It is reported that the attenuation of the MCD diet‐induced NAFLD by the treatment of 2,3,5,4′‐tetrahydroxy‐stilbene‐2‐O‐β‐D‐glucoside (TSG) was seemingly associated with the reduced abundance of Erysipelotrichaceae .…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Interestingly, it is claimed that drinking tea has a potential role in the treatment and prevention of liver injury caused by HFD. [29][30][31] A special Jing-Wei Fuzhuan brick tea is a unique post-fermented tea which is distinguished from the other post-fermented teas by deliberate fermentation with the probiotics Eurotium cristatum, and exhibits a variety of biological activities, such as antiobesity, antibacterial, and anti-oxidation effects. [12][13][14]32 A few reports have mainly focused on the investigation on anti-obesity and anti-oxidation properties of Fuzhuan brick tea, and limited study on the inuence of Fuzhuan brick tea against NAFLD is performed, and the regulatory effect of Fuzhuan brick tea on intestinal microbiota was also rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, kombucha modulates the immune system in animals, inducing the production of anti-inflammatory cytokines (e.g., IL-4 and TGF-β) and inhibiting the production of pro-inflammatory cytokines, such as IFN-γ and IL-17 (Haghmorad et al, 2020). The microbiome shift is one of the six fundamental changes in human bodies during spaceflights (Afshinnekoo et al, 2020), and it is already known that kombucha brew intake corrects changes in intestinal microbiota promoted by non-alcoholic fatty liver disease (Jung et al, 2019).…”
Section: Kombucha Dietary and Prophylaxis Projects During Spaceflightsmentioning
confidence: 99%